Research on key management and authentication protocol of PDA in smart grid - Xiao YU; Li TIAN; Zhe LIU; Jie WANG (网络与信息安全学报)
According to PDA in smart grid,which faced with security issues,key management and authentication protocol for PDA in smart grid based on scrambling PUF were presented.With the construction of mobile trusted platform by trusted hardware module and PDA,a key management mechanism was designed which presented for the indentify of hardware and controlled by user,to guarantee the security of key management and build a safe and effective mechanism of key backup and recovery.Based on trusted hardware module,security access for PDA in smart grid was realized,with the public and private key of key management strategy and improved access authentication protocol based on public key cryptography.